An Experimental–Theoretical Methodology to Develop Scuffing Limits for Relatively Smooth High-Speed Contacts. Issue 5 (20th August 2020) - Handschuh, Michael J.; Li, Sheng; Kahraman, Ahmet; Talbot, David
Abstract: In this study, a rough surface thermal elastohydrodynamic lubrication (TEHL) model tailored for the simulation of high-speed and high-temperature contacts of relatively smooth surfaces is introduced. The model uses a modified Carreau-Yasuda constitutive function to capture the non-Newtonian effects and a limiting shear formulation to consider any lubricant–solid slippage. It is employed to simulate a family of traction tests from Handschuh et al. for validation. According to the methodology of Handschuh et al., a set of two-disc scuffing experiments was performed with chemically polished surfaces under various rolling and sliding velocity conditions. Several load stages of these scuffing tests were simulated using the TEHL model with the measured surface roughness and bulk temperature as inputs. The predictions indicate that a scuffing limit based solely on the maximum surface or lubricant temperature does not exist for the contacts considered; however, a scuffing boundary based on both fluid temperature and contact pressure is evident.